1989
DOI: 10.2118/15707-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drilling Fluids on Rock Surface Properties

Abstract: Summary This paper discusses the wettability change induced by contact between porous media and drilling fluids and the possibility of eliminating such alterations by cleaning. Three porous media were studied (sandstone, shaly sandstone, and carbonate), as well as various drilling fluids (oil-and water-based). Initially strongly water-wet (hydrophilic) and initially neutral rock/oil/brine systems were evaluated. Wettability was estimated by a test based on spontaneous and forced displacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…However, depending on their droplet sizes, emulsions therein can invade reservoir rock and plug pores/pore throats, resulting in diminished hydrocarbon production [7][8][9]; moreover, surfactants which are added for generating emulsions can be adsorbed on rock surface and alter the wettability, which may also cause formation damage [7,10]. Besides the emulsions, suspended solids in the inverted emulsion, which is added for hindering leak-off, may also plug pores/pore throats; and this can make the formation damage even worse [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on their droplet sizes, emulsions therein can invade reservoir rock and plug pores/pore throats, resulting in diminished hydrocarbon production [7][8][9]; moreover, surfactants which are added for generating emulsions can be adsorbed on rock surface and alter the wettability, which may also cause formation damage [7,10]. Besides the emulsions, suspended solids in the inverted emulsion, which is added for hindering leak-off, may also plug pores/pore throats; and this can make the formation damage even worse [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Bobek et al (1958) and Amott (1959) both observed that oil-based muds make cores more oil-wet. Since then numerous studies have focused on the wetting effects of muds, their filtrates, or components of oil-based muds (Thomas et al, 1984;Gant and Anderson, 1988;Ballard and Dawe, 1988;Cuiec, 1989;Menezes et al, 1989;Yan et al, 1993;McCaffery et al, 2002;Skalli, 2003). Menezes et al (1989) examined the effects of commercial blends of surfactants on the wettability of quartz surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to using SBM contaminated cores is to clean the cores and restore to the original reservoir wetting conditions by re-exposure to reservoir fluids. The efficacy of cleaning processes has been studied for WBM and OBM-contaminated cores (e.g., Anderson, 1986;Cuiec, 1989), but studies of cleaning SBM-contaminated cores are limited (McCaffery et al, 2002). Gant and Anderson (1988) tested many common cleaning solvents and combinations of solvents for cleaning cores contaminated with invert emulsion oil-based muds.…”
Section: Spontaneous Imbibition With and Without Added Surfactantsmentioning
confidence: 99%